2021
DOI: 10.48550/arxiv.2103.02157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Deep and Wide Neural Network-based Model for Rajasthan Summer Monsoon Rainfall (RSMR) Prediction

Abstract: Importance of monsoon rainfall cannot be ignored as it affects round the year activities ranging from agriculture to industrial. Accurate rainfall estimation and prediction is very helpful in decision making in the sectors of water resource management and agriculture. Due to dynamic nature of monsoon rainfall, it's accurate prediction becomes very challenging task. In this paper, we analyze and evaluate various deep learning approaches such as one dimensional Convolutional Neutral Network, Multi-layer Perceptr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…WDNN has been used in various applications, such as clinical regression prediction for Alzheimer patients (Pölsterl, Sarasua, Gutiérrez-Becker, and Wachinger 2019). In the latest publication, (Bajpai and Bansal 2021) analyzed and evaluated three deep learning approaches, one dimensional Convolutional Neutral Network, Multi-layer Perceptron and Wide Deep Neural Networks for the prediction of summer monsoon rainfall in Indian state of Rajasthan and found that Deep and Wide Neural Network (DWNN) can achieve the best performance over the rest two deep learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…WDNN has been used in various applications, such as clinical regression prediction for Alzheimer patients (Pölsterl, Sarasua, Gutiérrez-Becker, and Wachinger 2019). In the latest publication, (Bajpai and Bansal 2021) analyzed and evaluated three deep learning approaches, one dimensional Convolutional Neutral Network, Multi-layer Perceptron and Wide Deep Neural Networks for the prediction of summer monsoon rainfall in Indian state of Rajasthan and found that Deep and Wide Neural Network (DWNN) can achieve the best performance over the rest two deep learning methods.…”
Section: Introductionmentioning
confidence: 99%